Sosialisasi Antisipasi Penyebaran Covid-19 melalui Buku Panduan dan Vidio Animasi Sebagai Penunjang Stabilitas Perekonomian Masyarakat di Kota Batam - Doni Putra Utama; Dwi Kartikasari; Shinta Wahyu Hati; Bambang Hendrawan; Yosi Handayani; Adhitomo Wirawan; Andi Erna Mulyana; Mia Syafrina; Ayu Puspitasari; Fandy Bestario Harlan (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
In early 2020, the world was shocked by the spread of new viruses, the new type of corona virus (SARS-CoV-2) and the disease called Coronavirus disease 2019 (COVID-19). Likewise, in the Riau Islands Province Particularly Batam City became a red zone affected by COVID-19, but there are still many local people who do activities to support their families. Based on the background described above, the service providers focus on making manuals and animation media so that COVID-19 prevention information is conveyed to the local community in order to maintain the economic stability of the community. The purpose of this Community Service Activity is to create, compile and distribute books. Covid-19 prevention non-authoritative guide so that people have awareness and participate in minimizing the spread of corona virus in Batam, designing and distributing animated videos of Covid-19 prevention guide so that people have awareness and participate in minimizing the spread of corona virus in Batam, socializing education guide books and animated videos so that people maintain health and safety in the Covid-19 Pandemic period, socializing educational guide books and animated videos to support the economic stability of the community. The Community Service Program of the Batam State Polytechnic Business Management program has been implemented and is running well which is participated by all groups and sectors in Batam City